A5.11 Vaccination against TNF and side effects in listeria infection model. (13th February 2015) - Belmellat, N; Faunonnier, L; Ryffel, B; Boissier, MC; Assier, E
Abstract : Background: Anti-TNF therapy has been a successful treatment strategy for rheumatoid arthritis disease, but is associated with reduced resistance to infection. Recently, active anti-TNF immunotherapy has shown its promising efficiency in a pilot phase IIA clinical trial. In mice, TNF is essential to control Listeria monocytogenes . We aimed at better defining the infectious risk/benefit ratio of TNF-a neutralisation of active immunotherapy strategy. For this purpose, we developed a vaccine (mTNF-K) targeting murine TNF-a by coupling the cytokine to the carrier protein keyhole limpet hemocyanin (KLH). We reported mTNF-K attenuated collagen-induced arthritis (CIA) to same extent as etanercept. Objectives: Here we evaluated the safety of TNF-a blockade induced by the vaccine in Listeria infection model. Materials and methods: 4 groups of 10 C57Bl/6 mice were used and compared with a murine TNF KO group (same background). Wild type mice were treated either by mTNF-K, etanercept, KLH or PBS. Vaccines were emulsified in CFA (day 0) or IFA (days 13, 27 and 40) before injections. All groups were infected at day 44 by 10 4 cfu of Listeria monocytogenes (LO28 strain). Mice groups were divided in two arms: one was euthanized 4 days post-infection, and the bacterial burden was evaluated in the spleen and the liver; survival of the lasting mice was evaluated until day 11. Blood sampling was conducted at day 34 and 47 in order to evaluate anti-TNF-a antibody production. Results: A sustained anti-TNF-a antibody production was obtained in mTNF-K vaccinated mice. At day 4 post-infection, mTNF-K and non-targeted-TNF-a treatments groups (KLH, PBS) presented lower bacterial burden in liver and spleen than TNF KO and etanercept groups. At day 11, all mice of PBS and mTNF-K groups survived to infection. Large lesions in livers were observed only within TNF KO and etanercept groups. Conclusions: Active immunotherapy with mTNF-K vaccine seems to preserve adequate host immunity against Listeria infection in this model.